Improving Reading Comprehension of First Year Engineering Students: A Quantitative Study at QUEST, Nawabshah, Pakistan - Mansoor, Ahmed Channa; Zaimuarifuddin, Shukri Nordin; Abdul Malik, Abassi (Canadian Center of Science and Education, 2018)
This paper reports the results of the research conducted to explore whether students learn reading comprehension more successfully using the different approaches based on strategies in reading texts. The study was conducted at QUEST, in Pakistan and the respondents were selected from four engineering departments. Data was collected through a set of questionnaire used as the qualitative instrument among 311 respondents. However, Questionnaire data was analyzed by using SPSS 17. Descriptive statistics were used to analyze research variables for producing the Percentages, Mean and Standard Deviation of the data. The findings of this study reported that this research investigated 18 categories of reading comprehension. The highest mean score in reading comprehension was for “read aloud practices” category (=2.40) rated by all respondents; while the mean score for “asking questions before, during, and after reading” (= 1.48) was the lowest. However, no category of reading comprehension fell into low level of usage. In short, results, discussion and recommendations are presented for developing effective reading strategies to design syllabus for the engineering students to improve their reading proficiency.